2020
DOI: 10.1016/j.joca.2019.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and osteoarthritis pain: common molecular mechanisms and potential therapeutic implications

Abstract: There is no clear evidence from epidemiological and animal studies of a direct link between metabolic syndrome (MetS) and cartilage degeneration in osteoarthritis (OA) once body mass index (BMI) has been considered. However, recent epidemiological studies indicate a significant role for MetS in predicting increased knee pain after adjustment for BMI. This implies there are mechanisms that underlie both MetS and OA pain. In addition to the common systemic inflammatory and pro-inflammatory components of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…60 Patientrelated factors such as stress, adverse life experiences, sex, gut microbiome, and comorbidities predispose to the development of central sensitisation and contribute to the pain phenotype. 7,24,93 3. The course of pain-like behaviour in rodent osteoarthritis…”
Section: The Course Of Pain In Human Osteoarthritismentioning
confidence: 99%
“…60 Patientrelated factors such as stress, adverse life experiences, sex, gut microbiome, and comorbidities predispose to the development of central sensitisation and contribute to the pain phenotype. 7,24,93 3. The course of pain-like behaviour in rodent osteoarthritis…”
Section: The Course Of Pain In Human Osteoarthritismentioning
confidence: 99%
“…A large number of studies focusing on analgesia have described the pain as the most prominent symptom of the disease and also the ability of the ECS to modulate pain in OA [ 302 ]. Mlost et al found that β-caryophyllene (a natural low-efficacy agonist of CB2r that is present in human diet) had both antinociceptive and chondroprotective effects in animals with experimentally induced osteoarthritis.…”
Section: The Endocannabinoid System and Aging-related Musculoskeletal...mentioning
confidence: 99%
“…It has been reported that molecular changes appear much earlier than apparent clinical symptoms (6). Hence, searching of biomarkers for OA has become a popular research trend (7). However, up to now, to the best of our knowledge, there have been no clinically applicable biomarkers in favor of the diagnosis, monitoring, and assessment the severity of OA owing to the heterogeneity in the pathogenesis and multiformity of clinical symptoms (8).…”
Section: Introductionmentioning
confidence: 99%